Designing E-Comic for English Learning Based on Needs Analysis: A Mixed-Methods Study of Vocational High School Students - Farid, Achmad; Yusuf, Adi; Kurniawan, Eddy; Syafrudin, Tomy; Baladina, Ashlaha; Faidah, Desi Nur; Ahmad, Fandi (Linguistics and ELT Journal, 2025)
Vocational high school (SMK) students have unique English learning needs compared to those in general schooling, as they require language skills relevant to their vocational fields such as computer, multimedia, and software development. Conventional English learning materials often fail to meet these needs because they lack contextual and engaging content. This study investigates the specific language needs, learning challenges, and media preferences of vocational students as a basis for designing digital learning materials, particularly e-comics, to support vocational English instruction. Adopting a mixed-methods design, data were gathered through questionnaires administered to 104 SMK students and semi-structured interviews with two vocational English teachers. The quantitative data identified vocabulary and comprehension as the most significant challenges, while the qualitative findings revealed students’ struggles in applying technical terminology and maintaining motivation during lessons. Students also emphasized the need for learning activities that promote active language use, such as conversation, storytelling, and task-based projects related to their fields of study. Both students and teachers expressed strong preferences for interactive and contextual learning media, noting that traditional textbooks often feel irrelevant to workplace communication demands. The integration of digital tools, particularly e-comics, was perceived as a promising approach to enhance engagement, vocabulary acquisition, and communicative competence. The study concludes that incorporating needs-based, contextually relevant, and visually appealing digital materials can significantly improve the effectiveness of vocational English learning and better prepare students for professional communication in their respective disciplines.